Practical Method of Tahfidz al-Qur'an for Early Childhood - Muthoifin, Muthoifin; Kurniawati, Ari (Prosiding University Research Colloquium, 2021)
This study focuses on the implementation of the Qur'an tahfidz program for early childhood using the Tabarak method at Rutaba Amanah Sragen and the Zahrawain method at the Tahfidz Toddler School Zahrawain Surakarta. This study aims to describe how the implementation of the tahfidzul Qur'an program for early childhood in each of these institutions, describe the supporting and inhibiting factors during the learning process, describe the comparison of the implementation of the two methods for the tahfidzul Qur'an program for early childhood. The method used in this study is a comparative descriptive study with a qualitative approach. Sources of data obtained from primary data and secondary data. Data collection techniques are observation, interviews, and documentation. The data analysis uses the stages of data reduction, data presentation, and concluding. The results of research at each institution include curriculum objectives, curriculum materials, targets for memorizing the Qur'an, implementation of methods, evaluation of learning as well as supporting and inhibiting factors for learning. The results of the research show that both methods utilize audiovisual media in the learning process, the Tabarak method which comes directly from Egypt has a more dense curriculum target than the Zahrawain method which adapts the capabilities of the Indonesian people. This is based on the time needed to memorize 30 juz of the Qur'an faster using the Tabarak method than the Zahrawain method.